Cannabinoid Therapeutic Effects in Inflammatory Bowel Diseases: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Antonio Vinci; Fabio Ingravalle; Dorian Bardhi; Nicola Cesaro; Sara Frassino; Francesca Licata; Marco Valvano (Biomedicines, 2022)
(1) Introduction: Inflammatory Bowel Disease (IBD) patients may benefit from cannabinoid administration supplementary therapy; currently no consensus on its effect has been reached. (2) Methods: a systematic review of RCTs on cannabinoid supplementation therapy in IBD has been conducted; data sources were MEDLINE, Scopus, ClinicalTrials. (3) Results: out of 974 papers found with electronic search, six studies have been included into the systematic review, and five of them, for a grand total of 208 patients, were included into the meta-analysis. (4) Conclusions: cannabinoid supplementation as adjuvant therapy may increase the chances of success for standard therapy of Crohn’s Disease during the induction period; no statement on its potential usage during maintenance period can be derived from retrieved evidence. Its usage in Ulcerative Colitis is not to be recommended. If ever, low-dose treatment may be more effective than higher dosage. Mean CDAI reduction was found stronger in patients treated with cannabinoids (mean CDAI reduction = 36.63, CI 95% 12.27–61.19) than placebo. In future studies, it is advisable to include disease activity levels, as well as patient-level information such as genetic and behavioral patterns.